Aquatic ferns from the Upper Cretaceous Loncoche Formation, Mendoza, central-western, Argentina - Puebla, Gabriela Griselda (2014)
Herein, we report new fossil remains with marsileaceous affinity associated with dispersed microspores corresponding to Crybelosporites, different types of massulae of Salvianiaceae (Paleoazolla patagonica and Azolla circinata), and a single megaspore assigned to the fossil genus Grapnelispora. These fossils were recovered from the Late Cretaceous Loncoche Formation, at the Calmu-Co section, Malargu¨e Group, Northern Neuque´n Basin, Mendoza, Argentina. The macrofossils include scattered leaflets, rhizomes, roots, and a sporocarp-like structure. They share characters with members of the aquatic fern family Marsileaceae; however, based on the characters preserved, they could not be placed within any extant or fossil species; therefore, the fossils are better included within a new fossil-taxon, Mendozaphyllum loncochense. Dispersed spores of Crybelosporites pannuceus, also belonging to Marsileaceae, were recovered from the entire section. Additionally, abundant isolated massulae with affinity to the aquatic fern family Salviniaceae, and a single megaspore assigned to Grapnelispora loncochensis, were identified from the plant bearing layer. The presence of Marsileaceae fossils in the Campanian?Maastrichtian Loncoche Formation, Mendoza, extends towards the north the paleogeographical distribution of the family Marsileaceae in Argentina, since previous records are from Patagonia. A fluvial to deltaic environment with lacustrine episodes is suggested by the sedimentology of the lower and middle parts of the Calmu-Co section and supported by the abundant fresh water algae recovered from the palynological association. This was probably the optimum habitat for the growth of aquatic ferns related to Marsileaceae and Salviniaceae and explains its abundance in the studied sediments.